Mechanism of Inflammation Regulation of α7nAChR in Spleen and Spinal Dorsal Horn of Mice with Paclitaxel-induced Neuropathic Pain by Electroacupuncture on Zusanli Acupoint - PANG Lina; LAN Yanyan; WANG Zhifu; CHEN Xiaomei; YU Xiangmei (康复学报)
ObjectiveTo investigate the effect of electroacupuncture on Zusanli acupoint on the inflammatory changes of α7 nicotinic acetylcholine receptor (α7nAChR) in spleen and spinal dorsal horn of mice with paclitaxel-induced neuropathic pain (PINP) .MethodsA total of sixty adult male C57BL/6 mice with the body weight of 18-22 g were selected and randomly divided into control group, model group, electroacupuncture group, intraperitoneal antagonist group and intrathecal antagonist group according to random number table, with 12 mice in each group. The model group, electroacupuncture group, intraperitoneal antagonist group and intrathecal antagonist group were injected with paclitaxel (2 mg/kg) every other day for a total of 4 times to establish the PINP model, while the control group was given the same amount of normal saline. After the model was established, the electroacupuncture group, intraperitoneal antagonist group and intrathecal antagonist group received electroacupuncture intervention once every other day from the first day, for 7 times in total. The intraperitoneal antagonist group and intrathecal antagonist group received intraperitoneal and intrathecal injection of α7nAChR receptor antagonist α-bungarotoxin (α-BGT) on day 1, 7 and 13, respectively. The changes of mechanical paw withdrawal threshold (PWT) and paw withdrawal latency (PWL) of mice at day 0, 7 and 14 were measured by Von Frey painometer and a plantar algesia meter, respectively. Western blot was used to detect the expression of α7nAChR protein in spleen and spinal dorsal horn of mice on day 14. RT-qPCR and ELISA were used to detect the mRNA and protein expression of TNF-α in spleen and spinal dorsal horn of mice on day 14.Results1) Behavioral test: There was no significant difference in PWT and PWL before the model was established in the five groups (P>0.05); PWT and PWL in the model group were significantly lower than those in the control group at day 7 and 14 (P<0.05). PWT and PWL in the electroacupuncture group were significantly higher than those in the model group at the 7th and 14th days (P<0.05). PWT and PWL in the intraperitoneal antagonist group and intrathecal antagonist group significantly decreased at the 7th and 14th day compared with those in the electroacupuncture group (P<0.05). 2) α7nAChR protein expression test: Compared with the control group, α7nAChR protein expression in spleen and spinal dorsal horn of the model group significantly decreased (P<0.05); compared with the model group, the α7nAChR protein expression in spleen and spinal dorsal horn of mice in the electroacupuncture group significantly increased (P<0.05). 3) TNF-α mRNA level and protein expression test: Compared with the control group, the mRNA level and protein expression of TNF-α in spleen and spinal dorsal horn of the model group significantly increased (P<0.05). Compared with the model group, the mRNA level and protein expression of TNF-α in spleen and spinal dorsal horn of the electroacupuncture group significantly decreased (P<0.05). Compared with the electroacupuncture group, the mRNA level and protein expression of TNF-α in spleen and spinal dorsal horn of mice in the intraperitoneal antagonist group and intrathecal antagonist group significantly increased (P<0.05).ConclusionElectroacupuncture on Zusanli acupoint may relieve the mechanical pain and thermal hyperalgesia in mice with PINP by up-regulating the expression of α7nAChR in spleen and spinal dorsal horn, and decreasing the release of inflammatory factor TNF-α in spleen and spinal dorsal horn.